Implementation of Digital Marketing at Mak Oteh Food Stalls - Chicha Rosha; Renny Christiarini (ConCEPt - Conference on Community Engagement Project, 2023)
This activity the author did with the aim of increasing revenue and customer visits and increasing public understanding of the existence of these food stalls. Warung Makan Mak Oteh is located at Pasar Angkasa, Nagoya Blok CC No 1 Batam, Riau Islands. As for some of the obstacles faced by restaurants, namely locations that are less strategic and only rely on the community around the location of the food stalls, so that customer knowledge about the existence of the restaurant is still weak and there is also no social media. accounts for sale so that no marketing promotions are carried out at the food stalls. or Mak Oteh's advertisements to attract customers to come shopping even though the products served are delicious. The implementation of the activities will take place from the beginning of October to the end of November 2022. The author has compiled several work plans that will be carried out on the implementation of activities related to digital marketing, namely the implementation of promotions in digital form that will be implemented, are already running and can be used for long-term performance. The initial stage that the author will do is to investigate the problems that occur in the business, find solutions to existing problems, design a more efficient system for the business, implement a new system plan in the business and explain the results obtained when operating the system. The activities carried out by the author have resulted in digital promotions that adapt to the problems faced by entrepreneurs such as a less strategic location. By implementing digital marketing, such as running promotions through their own social media accounts, digital marketing through paid advertising, and setting up a Google account business for Google Maps. The implementation of this new promotion system has a positive impact and also contributes to sales.